RETRACTED: The Effect of Compensation, Transformational Leadership, and Work Environment on the Performance of Ojju K-Food Restaurant Employees Jakarta - Anisya Latifa Sabasri; Herry Krisnandi; Kumba Digdowiseiso (Journal of Social Science)
This study aims to determine and analyze the effect of Compensation, Transformational Leadership and Work Environment on Employee Performance at Ojju K-Food Restaurant Jakarta. The data of this study used primary data in the form of a questionnaire to 102 employees of the Ojju K-Food Restaurant Jakarta. Data analysis techniques using multiple linear regression analysis and using the SPSS program. The results of this study indicate that there is an effect of compensation (X1) on employee performance (Y) of 0.332 and has an effect of 33.2%. Then the variable Transformational Leadership (X2) on Employee Performance (Y) is 0.134 and has an influence of 13.4%. Likewise for the variable Work Environment variable (X3) on Employee Performance (Y) of 0.403 and has an effect of 40.3%. Then to partially or simultaneously have a strong influence among the three variables, the most significant is the Work Environment variable of 0.000. The results of this study expect the company to be able to improve the work environment so as to help improve employee performance.